Correction of the sample temperature in the thermal analysis chamber for studying the kinetics of carbon oxidation - Kozlova Mariia; Donskoy Igor (E3S Web of Conferences)
This paper proposes a method for correcting the sample temperature under experimental conditions in the STA449F1 thermal analysis chamber. Carbon samples are oxidized in air-argon mixture, calorimetric signal is recorded and then processed to study the nutual interactions of heat transfer and chemical reaction. The technique is based on selecting the coefficients of the kinetic model and assessing its correctness using the simplest statistical metric.